Development, performance evaluation, and kinetic studies of microbial fuel cell based auto dripping bioelectrochemical reactor (AutoDriBER) for urine treatment - Mehrotra, Smriti (Environmental technology, 2024)
A bioelectrochemical reactor is an assembly, which facilitates energy generation and resource recovery using electrochemically active microorganisms. To maximise energy production from wastewater in this bioreactor system special design is required. Therefore, in the present study, continuous flow auto dripping bioelectrochemical reactors (AutoDriBERs) were developed as a single and multi-electrode assembly for urine treatment. Further, their performance was assessed by connecting reactors in series and parallel arrangements. AutoDriBER configured in series connection showed the highest 93.64 ± 1.57% chemical oxygen demand removal rate with the 1.38 ± 0.64 V voltage and 2.54 W m-3 polarisation power density. The optimum flow rate for maximum voltage production was tested with various models i.e. the linear, exponential, Sweibull-1, and Sweibull-2 models to confirm voltage prediction and its validity. The Linear and exponential models were found best fitted for voltage production with R2 value of 0.999. These findings infer a novel approach toward optimisation of the complex, inexpensive and self-sufficient design for electricity generation from energy-rich urine wastewater in rural areas